Contracts, firm dynamics and aggregate productivity - Bernabe Lopez-Martin; David Perez-Reyna (Banco de México, 2019)
We construct a framework of firm dynamics to evaluate the impact of the enforcement of contracts between final goods producers and their intermediate goods suppliers on firm growth, technology accumulation, and aggregate productivity. We build upon the static contracts model of Acemoglu et al. (2007), where the final goods firm chooses technology in contractible activities conducted by suppliers of intermediate inputs. Suppliers select investments in noncontractible activities, anticipating the payoffs that will result from bargaining with the producer of the final good. We show that contractual incompleteness implies a wedge on profits for producers of the final good, which discourages technology accumulation. Our model estimates differences in output per worker of up to 33% between economies with complete and incomplete contracts. The impact on firm growth, the age and size distribution of firms is quantitatively significant.
Keywords: D86; E23; O11; O40; 330; size-dependent distortions; contracts; aggregate productivity; firm dynamics